Detection method for underwater acoustic communication signals based on adaptive morphological filtering and Hough transform - WANG Yang; SHEN Tongsheng; WANG Tao; QIAO Gang; ZHOU Feng (Tongxin xuebao)
In order to solve the problem of underwater channel environment and severe noise interference in communication signal detection, based on structural characteristic (SC) of underwater acoustic communication signals, a detection method for underwater acoustic communication signals based on adaptive morphological filtering (AMF) and Hough transform (HT) was proposed. The short-time fractional Fourier transform (STFRFT) method was used to adjust the rotational angle in the fractional domain to match the signal phase, significantly improving the time-frequency energy concentration and forming a clearly defined band like SC. Based on the local density of pixel neighborhoods in time-frequency maps, AMF was constructed, which could dynamically adjust the scale factor of structural element to highlight signal detailed SC. HT model was established to detect banded SC through the global voting mechanism, thereby achieving efficient and accurate signal detection for underwater acoustic communication. The experment results show that the proposed method has better robustness and effectiveness in terms of generalization ability, detection probability, and detection efficiency under different channel environments.